Amphetamines Type Stimulant (ATS) Production and Trafficking In Southeast Asia Countries - Milda Istiqomah (Jurnal Risalah Hukum, 2010)
and trafficking in Southeast Asia countries. The objective of this article is to investigate organizational form and trafficking network of ATS within the region. Indonesia, Myanmar, and Cambodia will be used as analyzing case of the largest amphetamine producing and trafficking centre in the territory. The poverty, geo-strategic location, unstable sociopolitical situation and systemic corruption in law enforcement agencies are identified as the root of the emergence of multifaceted and transnational drugs trafficking in Southeast Asia. This article also provides suggestion on how to circumvent the impediments faced by the governments.